Methods of Bamboo Preservation and Effect of CCA in Green Round Bamboo - Prakash, Om; Singh, K. K.; Sood, Anil (Indian Forester, 2011)
Bamboos suffer from low shelf life because of attacks by fungi or insects mainly insect borers or termites. Traditionally, freshly cut bamboo poles were dipped in flowing water to remove starch, which attracts insects and pests or coating with oils or paint and even coal tar. The chemical method includes dipping in Cu SO4, Boric acid, Borax and Sodium pentachlorophenate solution to be used either singly or in combination. However, forcing out the sap under pressure and replacing with chemicals such as Copper- Chroma - Boric acid is a better method for enhanced shelf life. For small pieces, a treatment with hot and cold solutions of urea and Boric acid for varying periods has also been found quite useful.